Passivity control via Power Shaping of a wind turbine in a dispersed network - Peña, Ricardo Ramiro (2014)
The connection of renewable energy conversion systems in distribution networks must comply with codes for assuring power quality as well as the grid assistance demands. The new operating requirements cannot always be achieved from the control strategies that have been employed for years in conventional distribution systems. In this context, this paper addresses the problem of controlling a wind turbine from passivity control concepts. In particular a control strategy based on a new approach to the passivity theory, known as Power Shaping, is proposed. This approach allows to consider pervasive dissipation. The proposed strategy is evaluated in the context of extreme operating conditions showing capability to ride through grid failures. In this way, the simulation results encourage the application of concepts of Power Shaping in more complex systems of distributed generation.